2017
DOI: 10.1002/jobm.201600481
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of N‐butyl‐tetrahydro‐5‐oxofuran‐2‐carboxamide produced by Bacillus sp. L60 and its antifungal activity

Abstract: Rhizoctonia solani is the cause of substantial economic loss in many crops. The aim of this study is to investigate biocontrol potential of Bacillus sp. L60 against R. solani and to purify an antifungal compound. In this study, Bacillus sp. L60 demonstrated significant antagonism toward R. solani with the dual culture assay. The antifungal compound was extracted from Bacillus sp. L60 culture supernatant with n-butanol, and identified as N-butyl-tetrahydro-5-oxofuran-2-carboxamide (BT-5O-2C) having molecular we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Past studies on the antifungal activity of Bacillus revealed that Bacillus can produce defense-related antioxidant enzymes [9], N-butyl-tetrahydro-5-oxofuran-2-carboxamide [10], lipopeptide, protein [11], and other such antifungal substances. Interestingly, the content and type of volatile organic compounds (VOCs) possessing antifungal activities released by different Bacillus species during the growth process are extremely different [12][13][14].…”
mentioning
confidence: 99%
“…Past studies on the antifungal activity of Bacillus revealed that Bacillus can produce defense-related antioxidant enzymes [9], N-butyl-tetrahydro-5-oxofuran-2-carboxamide [10], lipopeptide, protein [11], and other such antifungal substances. Interestingly, the content and type of volatile organic compounds (VOCs) possessing antifungal activities released by different Bacillus species during the growth process are extremely different [12][13][14].…”
mentioning
confidence: 99%